Genetic Studies and QTL Mapping of Drought Related Traits in a Sweetpotato (Ipomea Batatas(L.) Bi-Parental Mapping Population - Utoblo, O.G. (University of Ghana, 2018)
The study was carried out to understand the genetic basis for yield under drought environments, and to map quantitative trait loci associated with yield and yield related components under drought stress in sweetpotato. The sweetpotato BxT mapping population, generated from a cross between sweetpotato varieties Beauregard and Tanzania was used for this study. Genotypes were evaluated in irrigated and drought environments to evaluate the effect of drought on yield and yield related parameters as well as genetic variability under drought conditions. Drought affected root yield, foliage yield, biomass and harvest index at varying degrees, with highest relative yield reduction in root yield. Drought tolerance indices were estimated based on root yield under drought and irrigated conditions. Suitable drought tolerance indices identified were geometric mean productivity, mean productivity and drought tolerance index. Genotypes were grouped as drought tolerant and high yielding (DTHY), drought tolerant and low yielding (DTLY), drought susceptible and high yielding (DSHY) and drought susceptible and low yielding (DSLY) based on their root yield means. Drought also reduced chlorophyll content, leaf area, normalized difference vegetation index (NDVI), photosynthetically active radiation, and increased canopy temperature. Observed low heritability and non-significant variation among genotypes for physiological traits indicates inefficiency of these traits for selection of drought tolerant genotypes in the BxT mapping population. However, morphological traits had significant variability among genotypes, high to moderate heritability under drought stress indicating they could be considered as potential secondary traits for selection of drought tolerant genotypes. To understand the genetic basis of drought tolerance in sweetpotato, QTLs associated with yield and yield related components under irrigated, drought and rainfed conditions were mapped using the genotype by sequencing method, GBSpoly. The occurrence of four QTLs on linkage group 9 in single environments and on linkage groups 11 and 6 for combined environments under only drought stressed conditions is indicative of drought specific QTLs. With further studies, confirmation and validation of these QTLs may be useful for drought tolerance-oriented breeding programmes in sweetpotato
PhD.
Keywords: Drought; Sweetpotato (Ipomea Batatas(L.)